2016
DOI: 10.4067/s0717-95022016000300010
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of the Macro and Microscopic Anatomy of the Sciatic Nerve in Wistar Rats

Abstract: . Aspects of the macro and microscopic anatomy of the sciatic nerve in Wistar rats. Int. J. Morphol., 34(3):877-884, 2016. SUMMARY:The present study seeks to systematize morphological and morphometrical parameters and brings new data on the main branch of the lumbosacral plexus -i.e., sciatic nerve -in Wistar rats aged four and seven weeks. Sixteen female were divided into two groups, namely animals aged four weeks, and animals aged seven weeks. The specimens were studied at proximal and distal segments of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
3
8
0
Order By: Relevance
“…12). Of note, axonal diameters for NF-200 positive neurons reported here do not include myelin and are in good agreement with previous literature (Suaid et al, 2016). Peripherin labelled neurons displayed much shorter stems, as compared to NF-200 positive neurons (60.7±4.2 m vs. 232.5±22.9 m, p<0.001; Fig.…”
Section: Does the Soma Have More Influence Over The T-junction In C-t...supporting
confidence: 92%
“…12). Of note, axonal diameters for NF-200 positive neurons reported here do not include myelin and are in good agreement with previous literature (Suaid et al, 2016). Peripherin labelled neurons displayed much shorter stems, as compared to NF-200 positive neurons (60.7±4.2 m vs. 232.5±22.9 m, p<0.001; Fig.…”
Section: Does the Soma Have More Influence Over The T-junction In C-t...supporting
confidence: 92%
“…The rat sciatic nerve exhibits a similar organization of specific axon populations. For instance, Suaid et al, 2016 ; Ravagli et al, 2020 both demonstrated that the axons contributing to the main branches of the sciatic (peroneal, tibial, and sural) stay discretely organized and do not intermingle for a significant distance proximal to the trifurcation. The same organization was found in the tibial branch of the sciatic nerve after retrogradely labeling individual distal branches contributing to small populations of muscles and tissue in the rat hindlimb ( Badia et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported in a variety of species that axons which serve specific distal branches of peripheral nerves travel in organized bundles along the course of the nerve ( Sunderland, 1978 ; Brushart, 1991 ; Hallin et al, 1991 ). The sciatic nerve of rats has been shown to exhibit a similar organization of its major branches ( Suaid et al, 2016 ; Ravagli et al, 2020 ) as well as its more distal branches ( Badia et al, 2010 ). We investigated the topographic organization of axons within the rat sciatic nerve at the level of an individual muscle (TA), and looked for consistencies in this topography bilaterally within animals as well as across animals and sexes.…”
Section: Introductionmentioning
confidence: 99%
“…In order to test the safety and efficacy of epineural injections, 3 experimental steps were designed using the rat sciatic nerve as a model because its diameter (1-1.5 mm) is similar to that of the human digital nerves [22].…”
Section: Experimental Designmentioning
confidence: 99%
“…The aim of this study is to identify a simple nerve staining technique which could aid intraoperative location of the digital nerve by improving its visibility and facilitating separation of the nerve from the Dupuytren's tissue. The rat sciatic nerve was used as a model in this study as its diameter is comparable to human digital nerves [22].…”
Section: Introductionmentioning
confidence: 99%